Neck circumference as a risk indicator for type 2 diabetes mellitus: a community based cross-sectional study - Arumugam, Balaji; R., Aadarshna; E., Suganya (International Journal Of Community Medicine And Public Health, 2019)
Background: Diabetes mellitus is a metabolic syndrome due to insulin deficiency, characterized by hyperglycaemia. Indian diabetes risk score (IDRS) is the most commonly used one to determine the risk status. However there is lot of inconvenience and possible errors in measuring the waist circumference to determine the IDRS, hence the study was planned to evaluate if neck circumference could replace waist circumference in determining the diabetes risk. Methods: This cross sectional study was conducted among 300 study participants fulfilling the eligible criteria. Socio-demographic variables, parameters required for determining the IDRS was assessed, in addition, neck circumference (NC) was measured using standard protocol. Another risk score was calculated by replacing waist circumference (WC) with neck circumference and scoring was named as IDRS-NC. Pearson correlation and Wilcoxan sign rank test was done to find out the relationship between WC and NC and also to determine if IDRS-NC could replace IDRS. Results: Out of 300 study population, majority of the participants are in the age group of <35 years 129 (43%) and around 2/3rd of the participants were females. Among the study participants proportion of participants belonging to low risk, medium risk and high risk assessed using IDRS and IDRS-NC was 18.7%, 41%, 40.3% and 31.7%, 38%, 30.3% respectively. There was a strong positive correlation (r=0.837) between the neck circumference and waist circumference. Wilcoxan sign rank test was significant between the 2 scores having a p value of <0.05. Conclusions: In our study there was a positive correlation between neck circumference and waist circumference.